2020
DOI: 10.1190/geo2019-0327.1
|View full text |Cite
|
Sign up to set email alerts
|

A field data example of Marchenko multiple elimination

Abstract: Internal multiple reflections have been widely considered as coherent noise in measured seismic data, and many approaches have been developed for their attenuation. The Marchenko multiple elimination (MME) scheme eliminates internal multiple reflections without model information or adaptive subtraction. This scheme was originally derived from coupled Marchenko equations, but it was modified to make it model independent. It filters primary reflections with their two-way traveltimes and physical amplitudes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Inversion of the Marchenko equation has proven to be an effective tool for the retrieval of Green's functions in an unknown acoustic medium from single-sided reflection data [1,2]. For an introduction to this subject, the numerical implementation of the Marchenko equation, field data applications and recent developments, see [3][4][5][6][7][8][9][10][11], respectively. An equivalent (Marchenko) equation has also been derived for wave propagation in elastic media [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Inversion of the Marchenko equation has proven to be an effective tool for the retrieval of Green's functions in an unknown acoustic medium from single-sided reflection data [1,2]. For an introduction to this subject, the numerical implementation of the Marchenko equation, field data applications and recent developments, see [3][4][5][6][7][8][9][10][11], respectively. An equivalent (Marchenko) equation has also been derived for wave propagation in elastic media [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Staring (2018) found that this information is not necessary, and the truncation time can be chosen independent of offset. Their work filters out primary reflections from acoustic data without using any model information and was successfully applied to field data (Zhang and Slob, 2020a). The scheme was adapted to remove free‐surface and internal multiples simultaneously (Zhang and Slob, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The MME scheme retrieves the primaries from the reflection data, while the T-MME retrieves the transmission compensated primaries from the upgoing filter function. The MME scheme has been tested on numerical and field data (Zhang and Slob, 2020a). The examples in show that all orders of internal multiple reflections are successfully eliminated by both schemes.…”
Section: Introductionmentioning
confidence: 99%